Reframing Syllabi as Aesthetic Encounters - Lockett, Michael; Wong, Gabriel (Journal of the Canadian Association for Curriculum Studies, 2018)
This academic work, which is comprised of three artefacts, responds to Maxine Greene’s “Spaces of Aesthetic Education” (1986). The main artefact is a syllabus, from an era of increasingly standardized syllabi, which imagines its aesthetic and educative attributes otherwise. In doing so, it reconsiders the kinds of learning a syllabus might prompt. It stems from a series of conversations we, the co-creators, shared about the ways curricular structures can come to prompt critical, creative and aesthetic attention. We had pursued those intersections in the past from our respective disciplinary perspectives and decided to collaborate on an art/research project, one that could inform and provoke a series of future curricular conversations. As our work unfolded, we spoke of curricular experiences that were meaningful and those were not and tried to articulate what we meant by “aesthetic experience”. We came to lament institutional demands for standardized curricular documents in our respective teaching contexts, especially mandated templates for syllabi. We wondered about the educative and aesthetic consequences of limiting their expression to a series of prescribed descriptors. Eventually we had an opportunity to experiment with the form through a fourth-year course on curriculum theory and practice, an ideal venue for introducing a parallel, yet supplementary, syllabus. That syllabus is displayed in full in this issue of the journal. It is also accompanied by an audio file and a corresponding transcription. Through that recording, we address some of the aesthetic considerations we incorporated into the design, delineate certain curricular choices, and explain the artefact’s discursive significance.